Study guides

☆☆

Q: What is y equals x 5x equals 12y?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

17

3x - 6y = 9, 5x + 4y = -27 6x - 12y = 18, 15x + 12y = -81 21x = -63 x = -3 (3 x -3) = 9 + 6y (-9 - 9)/6 = y y = -3 Check: (5 x -3) + (4 x -3) = -15 -12 = -27 QED

If: y = 5x and y = 3 -x Then: 5x = 3 -x => 5x +x = 3 => 6x = 3 => x = 1/2 By substitution point of contact is at: (1/2, 5/2)

y = 11

x=2 y=7 5x+3y= 5 7 x 2 x 3 ____ _____ 10 21 21 + 10 _______ 31

Related questions

5x=4012y=84124

10 z's.

If y equals 5x-15 and x equals 1 then the value of y comes out to be -10. So y equals 5x-15 is -10.

17

3x - 6y = 9, 5x + 4y = -27 6x - 12y = 18, 15x + 12y = -81 21x = -63 x = -3 (3 x -3) = 9 + 6y (-9 - 9)/6 = y y = -3 Check: (5 x -3) + (4 x -3) = -15 -12 = -27 QED

-5x + y = -12- 3x + 6y = -12Since both of expressions have a value of -12, their sum is - 24. This is true only whenx = 20/9 and y = -8/9.-5x + y = -12y = 5x - 12- 3x + 6y = -12-3x + 6(5x - 12) = -12-3x + 30x - 72 = -1227x = 60x = 60/27x = 20/9y = 5x - 12y = 5(20/9) - 12y = 100/9 - 12y = (100 - 108)/9y = -8/9

Add: 5x - y + x + y + 8 + 10 ie 6x = 18 so x = 3 and y = 7

x=6 y=30

-30

If: y = 5x and y = 3 -x Then: 5x = 3 -x => 5x +x = 3 => 6x = 3 => x = 1/2 By substitution point of contact is at: (1/2, 5/2)

5x²=0 X=0 the function y=5x² only intercepts x when x = 0

-5x=3+y x=-1/5y-3/5

People also asked